The Effect Of Executive Characteristics, CEO Overconfidence, And Capital Intensity On Tax Avoidance - Alissa Qotrunnada Fadia Zahra; Dul Muid (DIPONEGORO UNIVERSITY, 2025)
This study aimed to examine the effect of executive characteristics, CEO Overconfidence, and capital intensity on tax avoidance in manufacturing companies in the primary consumption sector. In this study, tax avoidance is the dependent variable, while executive characteristics, CEO overconfidence, and capital intensity are independent variables. Executive characteristics in this study are measured using risk, which uses the value of Earnings Before Interest, Taxes, Depreciation, and amortization (EBITDA) divided by total assets, CEO overconfidence is measured based on the size of his photo published in the annual report or company profile, capital intensity is measured using total fixed assets divided by total assets, and tax avoidance in this study is measured using Cash Effective Tax Rate (CETR). This study uses a quantitative approach using secondary data on manufacturing companies in the primary consumption sector obtained from the official website of the Indonesia Stock Exchange during the 2021-2024 period in the form of annual financial reports published by related companies. Using the purposive sampling method, 34 companies were collected which were then analyzed using multiple linear regression analysis tests using SPSS 25. The results of the tests show that executive characteristics has significant negative effect on tax avoidance, CEO Overconfidence has significant negative effect on tax avoidance, and Capital intensity has significant positive effect on tax avoidance.